Development of nanoemulsion containing Centella asiatica (L.) Urb crude extract as a promising drug delivery system for epilepsy treatment - L. Thuraisingam, Shobna (2021)
Preparations of products containing herbal extracts have grown by leaps and bounds hitting the pharmaceutical industries due to the natural healing approach. Centella asiatica (L.) Urb (pegaga) is a famous plant and is commonly served as a salad in Asian diets. It contains various phytoconstituents which plays a vital role in the treatment of various illness. For example, in the treatment of epilepsy, crossing the blood-brain barrier (BBB) has been a challenge (even as in parenteral application) and not all the drugs were able to pass through the membrane and produce a maximum therapeutic effect to the targeted site of action. Thus, nanoemulsion formulation containing C. asiatica crude extract needs to be developed in order to penetrate the BBB. C. asiatica crude extract was extracted in organic solvent (methanol and acetone) and the highest percentage yield was revealed in methanol extract (33.20 %) followed by acetone (15.90 %). Nanoemulsion was prepared by using the low-energy emulsification method. The particle size, polydispersity index (PDI) and zeta potential of C. asiatica crude extract-loaded nanoemulsion were found to be at 57.86 nm ± 0.03, 0.50 ± 0.03 and -26.50 ± 0.03 mV, respectively. The formulation remained physically stable at different storage temperatures (4.0, 25.0 and 45.0 °C) for 90 days. The particle size observed by transmission electron microscopy (TEM) was shown to be at ~50 nm, which correlated well with the Zetasizer analysis. The cytotoxicity study, which was conducted on formulated nanoemulsion towards Vero and 3T3 cell lines showed that the IC50 value indicated that it is nontoxic (>500 μg/ml) when compared to the crude extract alone which was 340 μg/ml against Vero cell line and 365 μg/ml in 3T3 cell line. The formulation was found to be stable based on the good evidence of physicochemical properties and the IC50 value indicate significance for future in vivo and in vitro studies based upon the route of administration.